Meanings attributed by university students to a teaching innovative experience based on social constructionism - Mª del Carmen Muñoz de Bustillo Díaz; Maria Dolores García Hernández; Evelyn Romero; Yexuanj Peláez Amador; Silvia Rodríguez Alonso (Universitat Politècnica de València, 2017)
Our study shows how students make sense of a teaching innovative experience at university, which develops the teaching-learning process based on social constructionism (Gergen, 2015).  Their judgements were analysed from the emic perspective (San Martín, 2014), using ATLAS.ti7 software for qualitative analysis. Students (26) express that they have lived through an unusual educational experience, being flexibility its main quality, a finding congruent with pedagogical proposals linked to the co-construction of knowledge. The meanings given by students revalue face-to- face education, as the classroom turns into the arena where unusual learning and a boom of ideas can take place, highlighting its usefulness as a relational space which nourishes collaborative creativity.  Challenges  also  emerge  and invite for further reflection on how to keep designing innovative education proposals at  universities  from  the  perspective  of relational  generation  of  knowledge.